2015
DOI: 10.3109/15360288.2014.1003674
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Does Not Decrease Intensity of Neuropathic Pain, but Improves Its Affective Dimension

Abstract: Recent understanding of the neuron-glia communication shed light on an important role of microglia to develop neuropathic pain The analgesic effect of minocycline on neuropathic pain is promising but it remains unclear in clinical settings. This study included 20 patients with neuropathic pain of varied etiologies. We administered 100 mg/day of minocycline for 1 week and then 200 mg/day for 3 weeks, as an open-label adjunct to conventional analgesics. An 11-point numerical rating scale. (NRS) and the short-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…The proposal that minocycline might be useful in treatment of depression is supported by the finding that minocycline suppressed depression-like symptoms also in non-diabetic conditions, such as when induced by mild foot shocks [105]. Importantly, in human subjects, minocycline treatment was able to reduce the affective dimension associated with traumatic neuropathic pain [106] further supporting the proposal that minocycline might be a treatment option in clinical conditions.…”
Section: Minocycline In the Control Of Diabetes-associated Emotional mentioning
confidence: 67%
“…The proposal that minocycline might be useful in treatment of depression is supported by the finding that minocycline suppressed depression-like symptoms also in non-diabetic conditions, such as when induced by mild foot shocks [105]. Importantly, in human subjects, minocycline treatment was able to reduce the affective dimension associated with traumatic neuropathic pain [106] further supporting the proposal that minocycline might be a treatment option in clinical conditions.…”
Section: Minocycline In the Control Of Diabetes-associated Emotional mentioning
confidence: 67%
“…The antiallodynic activities of BCP against ddC-induced mechanical allodynia were found to be similar to those of other immunomodulators, pentoxifylline and minocycline. However, BCP has the advantage of also directly attenuating established mechanical allodynia via CB2 receptors, whereas previous preclinical studies show that minocycline cannot attenuate established hyperalgesia and allodynia [78][79][80], which is possibly one of the reasons we postulated [50] for its failure in clinical trials for neuropathic pain [81]. Moreover, BCP alleviates allodynia in both female (current study and in another study [43]) and male mice [42], whereas a recent study showed that minocycline and pentoxifylline could reverse mechanical thresholds in males, but not in female mice [82].…”
Section: Discussionmentioning
confidence: 92%
“…Early work by Dubuisson and Melzack [ 20 ] and later work by Boureau et al [ 21 ] proposed anecdotal opinions that characteristic pain descriptions might discriminate against neuropathic pain; also, as these descriptions might result from particular mechanisms, specific management strategies could be applied. The use of some types of treatment modalities (e.g., pharmacotherapy, neurorehabilitation, and neuromodulation) clearly revealed that different pain-analgesic effects are observed for different pain characteristics; in other words, the analgesic effect depends on the pain characteristics [ 22 25 ]. For example, the ongoing, paroxysmal, and evoked pain characteristics measured on the NPSI would be sensitive to repetitive transcranial magnetic stimulation (rTMS), whereas dysesthesia/paresthesia is seldom sensitive to rTMS in patients with neuropathic pain [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other instances, in patients with phantom limb pain, mirror visual feedback treatment has been shown to improve the characteristic features of pain, which have been spontaneously described to associate with deep tissue-mediated pain (e.g., pressing, twisting, and cramp-like), but was not found to improve the characteristics of pain associated with the application of noxious stimuli to the skin surface (e.g., burning, stabbing, and pins and needles) [ 24 ]. Furthermore, minocycline was found to improve the affective characteristics evaluated on the McGill Pain Questionnaire [ 26 ], but did not alleviate the sensory characteristics [ 22 ]. In particular, a recent report involving the NPSI successfully demonstrated that the identification of subgroups of patients with distinct neuropathic pain characteristics should be encouraged in order to predict their differential responses to various pharmacotherapies, thereby indicating that heterogeneity among patient populations should be considered to allow a more stratified or even personalized treatment approach according to the pain characteristics [ 23 ].…”
Section: Discussionmentioning
confidence: 99%